2000
DOI: 10.1074/jbc.275.16.11921
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C-β and Oxygen Deprivation

Abstract: Fibrin deposition is a salient feature of hypoxemic vasculature and results from induction of tissue factor. Such tissue factor expression in an oxygen deficient environment is driven by the transcription factor Early Growth Response (Egr)-1. Using homozygous null mice for the protein kinase C ␤-isoform gene (PKC␤ null), PKC␤ is shown to be upstream of Egr-1 in this oxygen deprivation-mediated pathway for triggering procoagulant events. Whereas wild-type mice exposed to hypoxia (6%) displayed a robust increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…We previously reported that PKCβ −/− /ApoE −/− mice displayed less atherosclerosis than ApoE −/− mice and demonstrated links between activation of PKCβ and nondiabetic atherosclerosis. 10 In parallel, our previous findings revealed that activated PKCβ, especially βII isoform, is a critical upstream regulator of early growth response 1 (Egr-1) in response to vascular stress, such as hypoxia, 11, 12 ischemia/reperfusion 13 and nondiabetic atherosclerosis. 10 Egr-1, in turn, acts as a master switch coordinating expression of proinflammatory cytokines, chemokines, procoagulant molecules, cell adhesion molecules, and matrix metalloproteinase-2 (MMP-2).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…We previously reported that PKCβ −/− /ApoE −/− mice displayed less atherosclerosis than ApoE −/− mice and demonstrated links between activation of PKCβ and nondiabetic atherosclerosis. 10 In parallel, our previous findings revealed that activated PKCβ, especially βII isoform, is a critical upstream regulator of early growth response 1 (Egr-1) in response to vascular stress, such as hypoxia, 11, 12 ischemia/reperfusion 13 and nondiabetic atherosclerosis. 10 Egr-1, in turn, acts as a master switch coordinating expression of proinflammatory cytokines, chemokines, procoagulant molecules, cell adhesion molecules, and matrix metalloproteinase-2 (MMP-2).…”
Section: Introductionmentioning
confidence: 62%
“…Consistent with these observations, high glucose-induced increase in Egr-1 transcripts in U937 macrophages was blunted by the inhibitors of PKCβ, ERK1/2 and JNK, but not by the inhibitor of p38. Since Egr-1 has been demonstrated to play an important role in nondiabetic atherosclerosis 15, 30, 31 and it is one of the key downstream target genes of PKCβ and ERK1/2 or JNK in the response to hypoxia, 11, 12, 32 ischemia, 13 acute vascular injury 33, 34 and in nondiabetc atherosclerosis, 10 our current data suggest that PKCβ mediates upregulation of Egr-1, at least in part, via increased phosphorylation of ERK1/2 and JNK in early atherogenesis in diabetes. Furthermore, as there are two putative Egr-1 binding motifs in the proximal region of the CD11c (p150,95) promoter which may participate in the regulation of CD11c expression based on our TRANSFAC database search, 35 we examined the effects of high glucose-stimulated PKCβ-dependent signaling pathway on CD11 gene expression in U937 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…A cascade of events leading from Hmox-1 induction to CO generation, through an intermediary step of ERK phosphorylation, represses the Egr-1 ''master switch'' (12). Induction of Egr-1 by hypoxia (19) or ischemia (12) triggers procoagulant and inflammatory genes (12,13,19,26) such as TF, serpine-1, and IL-1␤. Modulation of these genes by CO (5, 10) may contribute to its clinically beneficial actions in lung transplantation (27).…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation of cells with AGEs has been shown to produce reactive oxygen species (56). Moreover, at high concentrations (1 mg/ml) HGA could induce NF-B activation (18).…”
Section: Figmentioning
confidence: 99%